En Bloc Partial Laminectomy and Posterior Lumbar Interbody Fusion in Foraminal Spinal Stenosis - Kim, Eung-Ha (Korean Society of Spine Surgery, 2009)
STUDY DESIGN: A retrospective study. PURPOSE: An en bloc partial laminectomy and posterior lumbar interbody fusion (PLIF) in spinal stenosis patients with severe foraminal narrowing has a shorter operation time, less neural manipulation and allows indirect decompression by restoring the interforaminal height compared to other procedures. This study investigated the efficacy of the procedure. OVERVIEW OF LITERATURE: PLIF is one of the most popular surgery for degenerative spine such as foraminal spinal stenosis, instability spondylolisthesis and discogenic pain. Various techniques for PLIF have their own advantages and disadvantages. But in some severe cases, we need an efficient method of PLIF for decompression and fusion. METHODS: This study examined 61 patients, who had 85 levels treated with PLIF using an en bloc partial laminectomy and facetectomy, and could be followed up for more than 2 years. The mean age of the patients and mean follow up period was 66 years and 39 months, respectively. The clinical results were evaluated using the MacNab's criteria, Visual Analogue Scale (VAS) score, and Korea Version Oswestry Disability Index (KODI). The union of the intervertebral space was evaluated using Lenke's criteria. The intervertebral angle and height of the posterior intervertebral disc were also measured. RESULTS: Excellent and good results were obtained in 54 cases (89%) according to MacNab's criteria. The VAS and KODI scores were 8.1 and 34.6, preoperatively, and 3.4, and 14.1, postoperatively. Bone union was A and B grades according to Lenke's criteria in 57 cases. The mean segmental angle and mean height of the posterior disc were respectively, 7.4° and 6.5 mm preoperatively, 9.1° and 10.6 mm postoperatively, and 8.0° and 9.7 mm in the last follow-up. There were 5 cases of postoperative infection, 4 cases of junctional problems and 1 case of screw malposition. CONCLUSIONS: En bloc partial laminectomy and PLIF is an effective method for treating severe spinal stenosis with foraminal narrowing.